2005
DOI: 10.1111/j.1365-2249.2005.02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of CD4+ T cell subpopulations in ANCA-associated vasculitis

Abstract: Summary In patients with ANCA-associated vasculitis (AAV), CD25 expression is increased on circulating T cells. Although in animal experiments the role of CD4+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 34 publications
7
50
0
1
Order By: Relevance
“…These abnormalities include lymphopenia [15], a high number of activated T lymphocytes in peripheral blood [16], skewing of Th1 to Th2 responses [17] and senescence of CD28 -lymphocytes in the CD8 + subpopulation [18]. Our results also demonstrate beneficial effects of DSG on T cells by inhibiting T cell receptor-mediated T cell proliferation and cytokine production in both Th1 and Th2 T cells.…”
Section: Discussionsupporting
confidence: 62%
“…These abnormalities include lymphopenia [15], a high number of activated T lymphocytes in peripheral blood [16], skewing of Th1 to Th2 responses [17] and senescence of CD28 -lymphocytes in the CD8 + subpopulation [18]. Our results also demonstrate beneficial effects of DSG on T cells by inhibiting T cell receptor-mediated T cell proliferation and cytokine production in both Th1 and Th2 T cells.…”
Section: Discussionsupporting
confidence: 62%
“…Louthrenoo et al (2) reported a low CD4/CD8 lymphocyte ratio in three of the six patients with KS and rheumatic disease. In total lymphocyte numbers and absolute/relative numbers of CD4 T-helper cells are low in patients with GPA compared with controls, irrespective of the disease activity (11). Therefore, low CD4-T helper state may play an important role in the pathogenesis of KS development.…”
Section: Discussionmentioning
confidence: 97%
“…These T-cells subsets are activated T-cells as well as Tregs (regulatory T cells) (38). Abdulahad et al reported an increase of CD25 high (Treg) CD4 T cells and CD25 low (activated T effector cells) cell populations in patients with Wegener's granulomatosis.…”
Section: Implications Of T-cell Immunity As Lesional and Circulatory mentioning
confidence: 99%
“…Circulating CD4+ CD25 T-cell population increases in AAV (36)(37)(38)(39). These T-cells subsets are activated T-cells as well as Tregs (regulatory T cells) (38).…”
Section: Implications Of T-cell Immunity As Lesional and Circulatory mentioning
confidence: 99%